Implementasi Metode Ceramah Interaktif dengan Kelompok Terbimbing untuk Meningkatkan Prestasi Belajar Siswa Kelas IX pada Materi Akhlak Terpuji pada Diri Sendiri - Rusmanidar, Rusmanidar (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2022)
This class action research aims to improve the learning achievement of students in class IX.2 at MTs N 3 Pekanbaru City in the odd semester of the 2021/2022 academic year through the implementation of the interactive lecture learning method with guided groups. The research was conducted with 4 stages of Kurt Lewin's PTK model consisting of planning, action, observation, and reflection. The research was conducted for 3 months from August to. October 2019 in 2 cycles, 1 cycle consisted of 2 meetings. To obtain valid data, data collection methods were carried out using triangulation techniques through observation, interviews, test instruments, and documentation. The main subject of the research was 35 students of class IX.2 supported by the teaching teacher, while the object of research was student learning achievement. The data analysis technique used descriptive quantitative analysis method. The indicators of the success of this study are seen from the results of the assessment of teachers and students which include: 1) The acquisition value of the observation of the teacher is at least 77, which is 80% of the total score of all assessment indicators; 2) Student learning achievement increases as seen from the number of student learning outcomes scores getting KKM ≥ 82 with a percentage of 85% of the total students in the class. The results of the study prove that the implementation of the interactive lecture learning method with guided groups is considered effective in improving student learning achievement, as evidenced by the value of the observation of the teacher has met the target provisions of the success indicator with the achievement of the final percentage value of 92%. This affects the overall increase in student learning achievement, and the acquisition of the final score of all students can reach the KKM, meaning that the research success indicator has been met with 100% student learning completeness